Pengaruh Metode Pembelajaran dan Kecerdasan Spasial Terhadap Hasil Belajar IPA Siswa - Sapiudin - (JTP - Jurnal Teknologi Pendidikan, 2014)
The objective of this research is to know the effect of learning method and spatial intelligence toward students. result in studying natural science. The study using 2 x 2 design level with 40 students at elementary School of Pulogadung 03 in the morning East Jakarta. The result of the study showed that there is interaction between learning Method used on spatial intellegence with students’ result in studying natural science (it means that the effect of learning method has corelation with students’ characteristic who involved in the learning procces. In this case, it can be said that there is no special learning method gives the effect to the students’ result in studying of natural science toward students with difference spatial intellegence. So that, the Science Teacher especially SDN Pologadung 03 in the morning should apply a few learning method to teach students with difference spatial intelligence.